Physicochemical Changes of Reused Cooking Oils Used to Prepare Potato Chips, Chicken, and Beef - Benard Nkole; Adolf Lungu; Christopher Mwanza; Evans Kaimoyo; Violet Kayamba; Evelyn Funjika (University of Sultan Ageng Tirtayasa, 2025)
The physiochemical characteristics of cooking oils can be altered by deep-frying techniques, which lowers the oil’s quality. In this study three different food types – potato chips, chicken and beef – were deep-fried using reused soya bean or sunflower cooking oils, and the physiochemical characteristics of the reused oil were measured after each round of frying. The study further compared the impact of reused cooking oil on the growth of Aspergillus flavus fungal colonies. By the 8th turn of frying the mean viscosity difference of beef reused cooking o il viscosity was 42.83 +/- 0.98 cSt, significantly different from the potato chips reused cooking oil at 21.62 +/- 1.26 cSt. For both reused soya bean and sunflower oil samples, the mean difference of AV and PV generally increased. This change in the AV and PV values was influenced by the type of food being prepared as well as the frequency of repeated use. Furthermore, media supplemented with reused oil leftover from beef frying cycles had significantly increased fungal growth in comparison to fungi grown on fresh oil supplemented media. Therefore, appropriate guidelines are required to monitor the quality of reused cooking oil and avoid health risks associated with using poor quality oils to prepare food for consumption.